2019
DOI: 10.1007/s42995-019-00005-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis on hepatic lipid metabolism and oxidative stress response in grass carp (Ctenopharyngodon idellus) fed a high-fat diet

Abstract: Bacillus subtilis is widely used in aquaculture as a probiotic. However, few studies have been conducted to examine the effect of B. subtilis on liver lipid metabolism. A total of 135 healthy grass carp (50.24 ± 1.38 g) were randomly divided into three groups: control (Con), high-fat diet (HF), and high-fat diet + B. subtilis (HF + B. subtilis), and fed for 8 weeks. The results showed that compared with the HF group, the weight gain rate (WGR) significantly increased (P < 0.05) and the hepatic lipid content, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Dietary inclusion of HF is known to induce oxidative stress and decrease antioxidant capacity in fish (Dai et al 2019;Zhao et al 2020;Zhou et al 2020). The present study confirmed this in Grass Carp that received the HF diet, as evidenced by lower activities of antioxidant enzymes (e.g., T-SOD and GPx) and a higher content of MDA, which is a biological marker of oxidative stress (Del Rio et al 2005).…”
Section: Dietary Sodium Butyrate Supplementation Increased Liver Anti...supporting
confidence: 84%
See 1 more Smart Citation
“…Dietary inclusion of HF is known to induce oxidative stress and decrease antioxidant capacity in fish (Dai et al 2019;Zhao et al 2020;Zhou et al 2020). The present study confirmed this in Grass Carp that received the HF diet, as evidenced by lower activities of antioxidant enzymes (e.g., T-SOD and GPx) and a higher content of MDA, which is a biological marker of oxidative stress (Del Rio et al 2005).…”
Section: Dietary Sodium Butyrate Supplementation Increased Liver Anti...supporting
confidence: 84%
“…However, Grass Carp farming in China has been encountering many serious problems, especially when high-fat (HF) diets are used (Gao et al 2011;Tang et al 2019). Dietary supplementation with excessive lipid (>9.6%) resulted in fatty liver syndrome (Du et al 2006), increased the liver oxidative stress response, and led to growth retardation and high mortality in Grass Carp (Zhao et al 2020;Liu et al 2021Liu et al , 2022. Consequently, there is an urgent need to solve the problems induced by HF diets in Grass Carp farming.…”
mentioning
confidence: 99%
“…Grass carp ( Ctenopharyngodon idella ) is one of the most popular farmed fish species in China, with a production of 5.5 million tons in 2019 ( Zhang et al., 2020 ). However, in the last few years, the aquaculture of grass carp has faced more and more challenges, including the adverse effects caused by the increasing application of high-fat diet (HFD) ( Tang et al., 2019b ; Zhao et al., 2019 ). Dietary fats play a vital role in fish nutrition and provide essential fatty acids, fat-soluble vitamins, phospholipids and cholesterol needed for normal growth, development and health maintenance of fish ( Jobling, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Four percent of lipid in the diet showed the protein-sparing effect, but 6% of lipid in the diet negatively affected growth performance and body composition of juvenile grass carp ( Du et al., 2005 ). The HFD leads to unnecessary liver fat deposition ( Wang et al., 2013 ) and oxidative stress ( Huang et al., 2018 ; Ma et al., 2018 ), which might consequently affect the health of fish and reduce the yield of fish ( Zhao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty liver and intestinal barrier damage are widespread in most farmed fish, which severely restrict the development of aquaculture ( 1 , 2 ). Therefore, there is an urgent need to develop green feed additives to maintain host liver and intestinal health.…”
Section: Introductionmentioning
confidence: 99%